INTEGRATION OF MULTICULTURAL ISLAMIC EDUCATION IN THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT ACTIVITIES AT STATE HIGH SCHOOL 1 PURWOSARI - Nirmawati, Alfani Apriliani; Nasir, Moch.; Marzuki , Ahmad (Jurnal Konseling Pendidikan Islam, 2025)
Integration of multicultural Islamic education through the Pancasila student profile strengthening project activities for students in schools aims to find out how the implementation of P5 is at SMA Negeri 1 Purwosari, and to find out how the integration of multicultural Islamic education in P5 activities. In this study, the researcher applied a descriptive qualitative approach, where the descriptive approach is interpreted as a formulation of problems that function as a guide to explore or describe the social situation being studied comprehensively, deeply, and thoroughly. The results show that the implementation of P5 at SMA Negeri 1 Purwosari is carried out through project-based learning with themes such as local wisdom, global diversity, sustainable lifestyle, entrepreneurship, and the voice of democracy. The challenges include time constraints, lack of resources, and differences in student understanding. SMA Negeri 1 Purwosari forms the multicultural character of students through various P5 themes and multicultural Islamic education activities, such as interfaith discussions, visits to places of worship, and social projects where all students are treated without distinguishing gender, ethnicity, or religion. This activity is expected to form the superior character of SMA Negeri 1 Purwosari students.